2008
DOI: 10.1055/s-2007-991108
|View full text |Cite
|
Sign up to set email alerts
|

Has Management of Epidermoid Tumors of the Cerebellopontine Angle Improved? A Surgical Synopsis of the Past and Present

Abstract: We compared the surgical outcomes of recent patients with cerebellopontine angle (CPA) epidermoids treated with advanced surgical tools with those of patients treated in earlier series. From November 2000 to June 2004, we treated 12 patients with epidermoid tumors. One patient had a strict CPA lesion. Tumors extended into the prepontine region in seven cases and supratentorially in two. In two cases the CPA was involved bilaterally. All patients but one underwent a lateral suboccipital approach in a semi-sitti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
1
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 32 publications
1
57
1
5
Order By: Relevance
“…Epidermoid cysts are benign tumors with slow growth that tend to envelop neurovascular structures without displacement (6,7). Symptoms depend on compression of these structures; often they cause trigeminal neuralgia or facial paresis if fifth or seventh cranial nerves are involved.…”
Section: Discussionmentioning
confidence: 99%
“…Epidermoid cysts are benign tumors with slow growth that tend to envelop neurovascular structures without displacement (6,7). Symptoms depend on compression of these structures; often they cause trigeminal neuralgia or facial paresis if fifth or seventh cranial nerves are involved.…”
Section: Discussionmentioning
confidence: 99%
“…9,11,37,38,40,45,48 Tuchman et al 45 most recently reported on the specific use of the endoscope in the removal of 9 CPA epidermoid tumors, 7 of them through a retrosigmoid approach, and 2 with a subtemporal approach. These investigators used an endoscopic-assisted technique with initial resection performed with the microscope and importantly report that additional tumor was identified with the endoscope in 85% of cases.…”
Section: Cranial Nerve Preop Deficit In Patients W/ Preop Deficits Inmentioning
confidence: 99%
“…Safavi-Abbasi et al 38 reported a series of 11 patients in which the endoscope was used for inspection following microscopic resection in epidermoid surgery. They advocated against the use of the endoscope for tumor dissection in epidermoids, recommending it to be used solely for inspection.…”
Section: Cranial Nerve Preop Deficit In Patients W/ Preop Deficits Inmentioning
confidence: 99%
“…Rozwijają się między trzecim a piątym tygodniem życia płodowego [2,3]. Występują w każdym wieku, jednak najczęściej są rozpoznawane w trzeciej-piątej dekadzie życia [3,4]. Torbiel naskórkowa jest wolno rosnącym łagodnym guzem, a jej najczęstszym objawem jest neuralgia nerwu trójdzielnego.…”
Section: Wstępunclassified
“…Ściana torbieli jest zbudowana z prawidłowych komórek naskórka [3]. Najczęstsze lokalizacje torbieli to kąt mostowo-móżdżkowy, okolica nadsiodłowa oraz okolica trzeciej komory [3][4][5]7].…”
Section: Dyskusjaunclassified